A Multi-Site Cross-Sectional Study of Anxiety Symptoms and the Associated Factors Among Chinese Drug Users Undergoing Compulsory Detoxification Treatment - Yang, Xiaoshi; Kovarik, Carrie; Wang, Yuke; Yu, Shenshui (Frontiers in Public Health, 2021)
Compulsory drug detoxification treatment (CDT) is currently the major drug rehabilitation modality in China, and drug users often suffer from extraordinary levels of stress during CDT, leading to a high prevalence of anxiety symptoms. The aim of this study was to assess anxiety symptoms of drug users undergoing CDT and explores the associated factors. This study was carried out in three cities in Liaoning, China with the cross-sectional design, using cluster sampling. About 900 CDT drug users accomplished the questionnaire in the face-to-face survey. Anxiety symptoms and related factors were assessed with hierarchical multiple regression (HMR) analysis. The prevalence of anxiety symptoms among the CDT drug users was substantially high (33.2%). HMR analysis indicated perceived stress and characteristics of drug use such as types of drugs, were the most important contributors to anxiety symptoms. Optimism (LOT-R) played a protective role in reducing anxiety symptoms in this population. Anxiety symptoms of drug users undergoing CDT were present in a significant proportion of the CDT population. Optimism is a protective factor which could attenuate the detrimental effects of perceived stress on anxiety symptoms and potentially improve treatment outcomes.